Label-Free Infrared Spectral Histology of Skin Tissue Part I: Impact of Lumican on Extracellular Matrix Integrity - Nannan, Lise; Untereiner, Valérie; Proult, Isabelle; Boulagnon-Rombi, Camille; Colin-Pierre, Charlie; Sockalingum, Ganesh D.; Brézillon, Stéphane (Frontiers in Cell and Developmental Biology, 2020)
Proteoglycans (PG) play an important role in maintaining the extracellular matrix (ECM) integrity. Lumican, a small leucine rich PG, is one such actor capable of regulating such properties. In this study, the integrity of the dermis of Lumican-deleted Lum-/- versus wild-type mice was investigated by conventional histology and by infrared spectral histology (IRSH). Infrared spectroscopy is a non-invasive, rapid, label-free and sensitive technique that allows to probe molecular vibrations of biomolecules present in a tissue. Our IRSH results obtained on control (WT, n=3) and Lum-/- (n=3) mice showed that different histological structures were identified by using K-means clustering and validated by HES staining. Furthermore, an important increase of the dermis thickness was observed in Lum-/- compared to WT mice. In terms of structural information, analysis of the spectral images also revealed an intra-group homogeneity and inter-group heterogeneity. In addition, type I collagen contribution was evaluated by HES and picrosirius red staining as well as with IRSH. Both techniques showed a strong remodeling of the ECM in Lum-/- mice due to the looseness of collagen fibers in the increased dermis space. These results confirmed the impact of lumican on the ECM integrity. The loss of collagen fibers organization due to the absence of lumican can potentially increase the accessibility of anti-cancer drugs to the tumor. These results are qualitatively interesting and would need further structural characterization of type I collagen fibers in terms of size, organization and orientation.